Uses of Organic Fabrics in Home Interiors - Mansi Gupta; Deepti Pande Rana; Suparna Sircar (International Journal of Environmental Planning and Development Architecture, 2023)
This paper explores the uses of organic fabrics in home interiors. Organic fabrics are gaining popularity in the field of interior design as more people become aware of the harmful effects that conventional fabrics have on the environment. These fabrics offer several benefits, including sustainability and durability making them a popular choice for interior designers. Organic fabrics can be used in various ways in home interiors, from bedding and curtains to upholstery and decorative items. The paper also discusses the challenges and limitations of using organic fabrics in home interiors, including availability, cost, and limited design options, and they can be more expensive than traditional fabrics. Despite these challenges, the use of organic fabrics in home interiors is expected to grow in the future, as technology improves to increase availability and design options. The study analyses the various types of organic fabrics available for use in home interiors, including cotton, linen, and wool, and compares them to conventional materials in terms of their durability, aesthetics, and environmental impact. Finally, the paper presents case studies and examples of successful implementation of organic fabrics in home interiors, showcasing the versatility and adaptability of these materials. Overall, this research paper provides insights into the benefits and opportunities associated with the use of organic fabrics in home interiors, highlighting their potential to transform the way we design and decorate our living spaces.
Keywords: Organic fabrics; eco-friendly; home interiors; sustainable